Listening is the Basis and Importance of Communication - Melibayeva Zarifa Umarovna (Genius Publishing Group, 2022)
In this article, it is spoken about listening which also serves as a powerful tool for teaching a foreign language. It makes it possible to master the sound side of the language being studied, its phonemic composition and intonation; rhythm, stress, and melody. Through listening, the lexical structure of the language and its grammatical structure are assimilated
Keywords: Listening; communication; skills; language